3D bioprinting innovation and the patentability hurdle: Patents - Devarapalli, Pratap; Nicol, Dianne; Nielsen, Jane (Nature biotechnology, 2025)
How are patent examiners in the United States, Europe and Australia interpreting and applying the patentability criteria to specific subject matter related to 3D bioprinting technologies?